Empiriske metoder i sprogvidenskabelig forskning - Bergenholtz, Henning (HERMES - Journal of Language and Communication in Business, 1988)
I presume an interdependent connection between the empiric basis chosen for linguistic research and the possible methods used by the linguist. Considering that the use of self-made (often unnatural) sentences and the reliability of linguistic tests are dubious methods, the ananlysis of texts will be the best method in all difficult cases.